Strongly b star(Sb*) – cleavability(splitability) - Jallalh, Ghazeel A. M. (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
A. Poongothai and R. Parimelazhagan[5] introduced some new type of seperation axioms and study some of their basic properties. Some implications between T_0, T_1and T_2 axioms are also obtained. In this paper we studied the concept of cleavability over these spaces: ( sb*-T_0, sb*-T_1, sb*-T_(2 )) as following: 1- If P is a class of topological spaces with certain properties and if X is cleavable over P, then X∈P 2- If P is a class of topological spaces with certain properties and if Y is cleavable over P, then Y∈ P.